Synthesis and physical properties of tunable aryl alkyl ionic liquids based on 1-aryl-4,5-dimethylimidazolium cations - Fritsch, Stefan; Strassner, Thomas (Beilstein Journal of Organic Chemistry, 2024)
We present a new class of tunable aryl alkyl ionic liquids (TAAILs) based on 1-aryl-4,5-dimethylimidazolium cations with electron-withdrawing and -donating substituents in different positions of the phenyl ring and the bis(trifluoromethylsulfonyl)imide (NTf2) anion. We investigated the effect of additional methyl groups in the backbone of the imidazolium core on the physical properties regarding viscosity, conductivity and electrochemical window. With an electrochemical window of up to 6.3 V, which is unprecedented for TAAILs with an NTf2 anion, this new class of TAAILs demonstrates the opportunities that arise from modifications in the backbone of the imidazolium cation.
Keywords: conductivity; electrochemical window; ionic liquids; tunable aryl alkyl ionic liquid; viscosity